Effektivisering eller social omsorg - En kvalitativ studie om första linjens chefers syn på välfärdsteknik i äldreomsorgen - Hagedorn,Rebecca; Bernmarker Olsson,Cassandra (2026)
The purpose of this study was to examine how first-line managers in elderly care work with and reason about the use of welfare technology, specifically focusing on the balance between demands for efficiency and ensuring good social care. To address the study's aim and research questions, a qualitative method was applied, consisting of four semi-structured interviews with an operations manager and group managers within a single organization. The theoretical framework was based on Max Weber's theories on bureaucracy and rationalization, alongside Aaron Antonovsky's theory of Sense of Coherence (SOC/KASAM). This study found that managers view welfare technology as a valuable support system that can contribute to time savings, increased safety, and the promotion of users' autonomy and independence. At the same time, significant challenges were identified, such as staff resistance to change (particularly among older generations), technical vulnerabilities leading to double work during outages, and an ethical concern that human contact and relational values risk being replaced by technical solutions. The study highlighted how managers operate within a field of tension between a rational logic striving for standardization and efficiency, and a care-ethical logic focused on preserving the user's sense of meaning and quality of life. The conclusion pointed to the importance of thorough implementation and participation to ensure that technology benefits staff, users, and the organization as a whole without losing the human dimension of care.
Keywords: welfare technology; first-line managers; elderly care; efficiency; social care